2010
DOI: 10.1021/jp101149k
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic Properties of Internally Mixed Particles of Ammonium Sulfate and Succinic Acid Studied by Infrared Spectroscopy

Abstract: Atmospheric aerosols typically consist of inorganic and organic material. Although the organic fraction can affect the behavior of mixed organic/inorganic particles, their physical properties are not well-understood. In this work, infrared spectra of internally mixed submicrometer particles of ammonium sulfate and succinic acid have been studied at ambient temperature in an aerosol flow cell. The spectra of dried particles show distinct features relative to the pure components, as a result of ion-molecule inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…The configuration of the experimental setup used in this work is based on a previously described system (Minambres et al, 2010) that has been modified for the present study. The main elements are depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The configuration of the experimental setup used in this work is based on a previously described system (Minambres et al, 2010) that has been modified for the present study. The main elements are depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[40] A final consideration is that the hygroscopic behavior of particles of mixed composition, containing inorganic species together with soluble organic compounds, can differ from that of single-component aerosols. There is no clear consensus in the literature, with both increases and decreases in DRH values having been reported for mixed aerosols, compared to those containing inorganic substances alone [Choi and Chan, 2002;Miñambres et al, 2010;Wu et al, 2011;Zhang et al, 2011]. The chemical measurements (Table 2) showed that WSOC contributed 66.5%, on average, to the total mass of the soluble aerosol species measured, so that the existence of internal mixtures of inorganic compounds and WSOC could potentially affect aerosol growth rates.…”
Section: Influence Of Aerosol Composition On Water Uptake Capacitymentioning
confidence: 98%
“…Furthermore, the authors demonstrated a higher productivity in the cultivation of P. sativum using 25% P. amboinicus leaf extract. Several biological activities have previously been attributed to the isomeric chemotypes thymol and carvacrol, such as antifungal activity [33][34][35][36], insecticide, phytotoxic among others [33,37].…”
Section: Bioherbicidal Assaysmentioning
confidence: 99%